Peran Kurikulum Pendidikan Agama Kristen dalam Meningkatkan Spiritualitas Pemuda - Agustinus Tandi la’bi’; Semuel Linggi Topayung (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to explore the role of the Christian Religious Education (PAK) curriculum in improving the spirituality of youth in Indonesia. Using a qualitative approach, this study involved in-depth interviews with teachers, students and practitioners of Christian Religious Education to obtain a holistic perspective regarding the influence of the curriculum on the formation of the spirituality of the younger generation. The research results show that the PAK curriculum has an important role in instilling moral values, strengthening faith, and forming the character of Christian youth. The implementation of a relevant and contextual curriculum allows young people to understand and appreciate religious teachings more deeply, so as to improve the quality of their relationships with God and each other. This research also found that there are challenges in implementing a curriculum that is able to adapt to current developments and technology without ignoring the substance of spirituality. Therefore, the success of the PAK curriculum in increasing youth spirituality is highly dependent on the active involvement of educators and educational institutions in creating an environment that supports learning that is holistic and relevant to the spiritual needs of today's youth.